Two new species of Campanula (Campanulaceae) from the island of Santo Antão, Cabo Verde archipelago - Gardère, Mathieu Laurent (Phytotaxa, 2015)
Two new species Campanula feijoana and Campanula hortelensis, long identified as C. jacobaea, are described and illustrated. The news species are endemic to the island of Santo Antão (Cabo Verde archipelago) and morphologically close to C. jacobaea, but are distinguishable by their unique floral characteristics. Some of these distinguishing features are shared between C. feijoana and C. hortelensis, i.e. narrow triangular sepals, and a tubular corolla constricted around the middle part with explanate or revolute lobes.